2006
DOI: 10.1254/jphs.fp0050980
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Induces Apoptosis by Activation of Caspase-3 in Cultured Cardiomyocytes In Vitro and Rat Cardiac Ventricles In Vivo

Abstract: Abstract. Doxorubicin (DOX) is widely used to treat patients suffering from cancer, but the usage for patients is limited because of the dose-dependent cardiotoxicity. We hypothesized that DOX induces apoptosis through caspase activation in cardiomyocytes, and we examined this hypothesis using both rat primary cultured cardiomyocytes and rat hearts from an animal model. Cardiomyocytes were treated with DOX for 24 h. The activity of caspase-3 was significantly increased by DOX treatment. In rats with DOX inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
104
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 31 publications
14
104
1
1
Order By: Relevance
“…It is pertinent to speculate that the same effects could be attained in vivo using a subchronic or chronic treatment with lower, pharmacological doses due to tissue drug accumulation. In fact, most alterations induced by Dox on H9c2 myoblasts, such as mitochondrial and nuclear damage, cytoplasm vacuolization, alterations in sarcomeric proteins, and apoptosis, are indeed observed in cardiac tissue after in vivo Dox treatment (Grimmond and Beerman 1982;Iwasaki and Suzuki 1991;Jang et al 2004;Jones et al 1990;Ueno et al 2006;Unverferth et al 1981;Villani et al 1990). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is pertinent to speculate that the same effects could be attained in vivo using a subchronic or chronic treatment with lower, pharmacological doses due to tissue drug accumulation. In fact, most alterations induced by Dox on H9c2 myoblasts, such as mitochondrial and nuclear damage, cytoplasm vacuolization, alterations in sarcomeric proteins, and apoptosis, are indeed observed in cardiac tissue after in vivo Dox treatment (Grimmond and Beerman 1982;Iwasaki and Suzuki 1991;Jang et al 2004;Jones et al 1990;Ueno et al 2006;Unverferth et al 1981;Villani et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Caspase 9 is control relatively to healthy (asterisk) and apoptotic cells dependent on the mitochondrial pathway for apoptosis (Garrido et al 2006;Schafer and Kornbluth 2006), confirming that mitochondria are involved in Doxinduced toxicity on H9c2 myoblasts. In fact, both mitochondrial-dependent (Ueno et al 2006) and mitochondrial-independent (Jang et al 2004) pathways have been described as involved in in vivo apoptosis induced by Dox in cardiac cells. LDH release assays also confirmed that Dox causes cell death, although the method itself measures necrosis, which can occur in vitro sequentially to apoptosis induction or occur as a primary event.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were stimulated with ADR, 3 g/ml (5 M) for 3 d. 42,43 Supernatants were retrieved for AGE ELISA. In other studies, podocytes were stimulated with S-100B.…”
Section: Cell Culturementioning
confidence: 99%
“…Apoptosis has been identified in various cardiac disease states, for example, in ischemia and reperfusion injury (Krijnen et al 2002;Eefting et al 2004;Matsushita et al 2005;Liang et al 2006) or doxorubicin toxicity (Ueno et al 2006). Evans blue staining of myocytes has been associated with apoptosis in muscular dystrophy (Matsuda, 1995).…”
Section: Introductionmentioning
confidence: 99%